Experimental and CFD modelling of a Progressive Cavity Pump using overset unstructured mesh - Becerra Deisy (EDP Sciences, 2021)
A Progressive Cavity Pump (PCP) is widely used in industry as an artificial lift method because of its high efficiency during the pumping of high viscosity fluids and two-phase liquid-gas flow slurries. However, modelling PCP through Computational Fluid Dynamics (CFD) is quite complicated since it requires a meshing algorithm and is computationally expensive. Therefore, this study's main objective is to develop a CFD model capable of predicting a progressive cavity pump's behavior by implementing the Overset Mesh, which includes the relative motion between the rotor and the stator. Overset meshes are used to discretize a computational domain with several different meshes that arbitrarily overlap each other. They are most useful because the rotor geometry can be enclosed in a fluid (background) region and set to different positions. The PCP analyzed in this study is a GRP 4.0-4000 208 TSL 1-2 mono-lobe, which contains an API J55 stainless steel rotor and stator handling four Newtonian fluids (water, oil API 11, oil API 22, and oil API 31) at three rotational speeds (100 rpm, 150 rpm, and 200 rpm). The experimental data presented in this paper was collected in the PCP experimental facility of the SLACOL BCP Group (Tenjo, Colombia). All the measurements were made using the CILA2S controller for artificial lifting in the underground and on the surface to determine the operational curves of flowrate, volumetric efficiency, torque, and power consumed. The CFD model implementation was developed on Star- CCM+ version 15.02-R8 of 2020 for laminar and turbulent regimens. The results obtained through this study show that it is unnecessary to program a structured mesh to capture a progressive cavity pump's performance since the operational parameters evaluated to have an accuracy of 10% concerning the experimental data.Similarly, capturing the viscous effect near the wall and the transversal y horizontal slip inside the cavities is possible. The flow rate obtained for higher viscosity oils is more significant for the same pressure differences for water with average volumetric efficiencies of 85%. Finally, the pressure increase per stage is homogeneous along the pump's entire length for all fluids evaluated